Association between the Fatty Liver Index and Risk of Type 2 Diabetes in the EPIC-Potsdam Study. - Susanne Jäger; Simone Jacobs; Janine Kröger; Norbert Stefan; Andreas Fritsche; Cornelia Weikert; Heiner Boeing; Matthias B Schulze (PLoS ONE, 2015)
The fatty liver index (FLI) predicts fatty liver by using BMI, waist circumference, γ-glutamyltransferase and triglycerides. We investigated the association between the FLI and the risk of type 2 diabetes and evaluated to what extent single FLI components contribute to the diabetes risk. We analysed a case-cohort study (random sub-cohort: 1922; incident cases: 563) nested within the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam study. The proportion of exposure effect (PEE) explained by single FLI components was evaluated and effect decomposition using inverse probability weighting (IPW) was applied. Women and men with a FLI ≥ 60 compared to those with a FLI < 30 had a multivariable-adjusted Hazard Ratio (HR) of 17.6; 95% confidence interval (CI) 11.1-28.0 and HR: 10.9; 95% CI 6.22-19.2, respectively. Adjustment for BMI or waist circumference attenuated this association in men [PEE BMI (95% CI) = 53.8% (43.9%-65.8%); PEE waist (95% CI) = 54.8% (44.2%-68.8%)]. In women, adjustment for waist circumference attenuated the association to a lesser degree than in men [PEE waist (95% CI) = 31.1%; (21.9%-43.1%)] while BMI had no appreciable effect [PEE BMI (95% CI) = 11.0% (2.68%-21.0%)]. γ-glutamyltransferase and triglycerides showed only a small attenuation in women [PEE GGT(95% CI) = 3.11% (-0.72%-4.48%); PEE TG (95% CI) = 6.36% (3.81%-9.92%)] and in men [PEE GGT = 0%; PEE TG (95% CI) = 6.23% (2.03%-11.8%)]. In women, the total effect was decomposed into a direct effect and 4 indirect effects (HR BMI = 1.10; HR waist = 1.28; HR GGT = 0.97 and HR TG = 1.03). In men, the 4 indirect effects were HR BMI = 1.25; HR waist = 1.29; HR GGT = 0.97 and HR TG = 0.99. These data suggest that the FLI, as a proxy for fatty liver, is associated with risk of type 2 diabetes. This association is only partly explained by standard estimates of overall and abdominal body fatness, particularly among women.